The Pending and Relative Ineffectiveness in Three Interpretive Decisions of the Supreme Cassation Court - Tsoneva, Silvia (Yearbook of the Law Department, 2021)
The article examines pending and relative ineffectiveness of contracts in the case of Art. 76 of the Inheritance Act, Art. 26 of the Family Code and Art. 42 of the Obligations and Contracts Act as treated in interpretative decisions No. 1 of 19.5.2004, No. 5 of 29.12.2014 and No. 5 of 12.12.2016 of the Supreme Cassation Court. The concept and types of ineffectiveness are analyzed, as well as the specific issues of the situations discussed. It is concluded that Art. 76 IA provides for a resolutive condition combined with relative ineffectiveness, Art. 24, para. 4 and Art. 26 FC – contestability, which is different from relative ineffectiveness, and Art. 42 of the Obligations and Contracts Act – pending ineffectiveness, but in the absence of confirmation the possibility the contract to become effective is finally lost, and any interested person can invoke it.